(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examines the electoral system and its relationship to political transformation, considering electoral systems as among the most important means by which democratic systems regulate the transfer of power and achieve political participation. The study aims to demonstrate the impact of electoral systems on achieving political stability and strengthening democracy within a state. It addresses the evolution of methods for assigning power, illustrating the transition from traditional systems of governance to modern democratic systems based on the principle of elections and universal suffrage. The study also examines the conditions for the right to vote, the preliminary procedures for the electoral process, and reviews the most important contemporary electoral systems, outlining the advantages and disadvantages of each system and its impact on political representation and political life.